Pemberdayaan Kader dalam Mendeteksi Dini Kanker Serviks Melalui Metode Pap Smear di Kecamatan Sukawati (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2025)
Cervical cancer is a cancer that grows in the cervix, originating from the epithelium, or outer surface layer of the cervix, and 99.7% is caused by the HPV virus (Human Papilloma Virus), the HPV virus most often identified in cervical cancer is HPV types 16 and 18. Based on interviews with community service cadres, it was found that partners have minimal knowledge about cervical cancer prevention. In addition, partners still have a lack of knowledge about cervical cancer prevention programs through the Pap Smear program. Overall, this community service program has shown that with the right approach and continuous support, cervical cancer prevention efforts through women's empowerment through early detection programs with Pap Smears can have a significant positive impact on fertile women in Sukawati District. This program indicates that empowerment through education and early detection has great potential in reducing the rate of cervical cancer among women of childbearing age. Increasing knowledge and willingness to undergo Pap Smear screening is a crucial first step. However, the sustainability of the program is highly dependent on cross-sectoral commitment from local governments, health facilities, civil society organizations, and the community of women of childbearing age themselves. The community service team's recommendation is to integrate the Pap smear program into broader reproductive health services in other sub-districts.
Keywords: Empowerment; Cadres; Cervical Cancer; Pap Smear; Sukawati